Performance of Photovoltaic Systems with Solar Tracking in Singapore - Amin, Zakaria Mohd.; Maswood, Ali I.; Hawlader, Mohammad Nurul Alam; Al-Ammar, Essam A.; Orfi, Jamel; Al-Ansari, Hany A. (2012)
Photovoltaic technology enables direct conversion of solar irradiation into electricity. This project investigated the performance of a single-axis active solar tracking system by constructing and testing. From the results, it was observed that the output current varied almost instantaneously with the irradiation whilst the output voltage remained fairly constant even with huge fluctuations in irradiation. The efficiency of the solar panels was found to be 11.9% for the tracking configuration. This represented a 33.6% increase in efficiency when using the single-axis tracking system over the fixed ones.